HUBUNGAN AKTIVITAS FISIK DENGAN KEJADIAN OBESITAS PADA ORANG DEWASA DI INDONESIA (Analisis Data Riskesdas 2007) - Sudikno .; Milla Herdayati; Besral . (GIZI INDONESIA, 2010)
ASSOCIATION BETWEEN PHYSICAL ACTIVITY AND ADULT OBESITY IN INDONESIA(Secondary Data Analysis of the Basic Health Research 2007) The enhancement of social economy status and the life style changes, including changes in eating habits and reduction of physical activities, increased overweight and obesity revalence. This paper aims to study the association between physical activity and adult obesity in Indonesia. This research used Basic Health Research (Riset Kesehatan Dasar) 2007 data with cross-sectional design. The populations were all household members aged ≥ 18 years, whereas the samples were all household members aged ≥ 18, physically and mentally healthy, non-pregnant, and their BMI were at least 18.5 kg/m 2. The respondent was obese if his/her BMI was at least 18.5 kg/m2. Physical activity was assessed with questions about its type (vigorous and moderate) and its duration per week. Logistic regression was used to study the relationship between physical activity and adult obesity. The result showed that Obesity prevalence (BMI27kg/m2) in adult was 12.47% (CI 95%: 12.28 – 12.66). The result showed tthere was a relationship between physical activity and adult obesity, controlled by confounder variable (area, age, sex, marital status, education, occupation, and smoking habits). People who had low level of physical activity had more risk to be obese than those who had high level physical activity. It has been recommended that to reduce the risk of being obese, it is advisable to have sufficient physical activity such as alking, jogging, running, and biking. It is also necessary for the Ministry of Health to develop guidance of sufficient physical activity.Keywords: obesity, adult, physical activity